2022
DOI: 10.1055/a-1942-2447
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Retention Rate, and Influencing Factors of Ketogenic Diet Therapy in Children with Refractory Epilepsy: A Retrospective Study

Abstract: Aim This study aimed to evaluate the efficacy and retention rate of a ketogenic diet (KD) and assess factors that influence the efficacy of KD therapy in children with refractory epilepsy (RE). Methods We retrospectively studied the efficacy and retention rate of 56 RE children who accepted KD therapy from January 2013 to December 2019. Patients who had a ≥50% reduction in seizure frequency were defined as responders. The retention rate was calculated as the proportion of children who continued KD/the total nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Nevertheless, the response rate observed in our study was lower than that reported by other studies which ranged between 70% and 90% 22,23 . The retention rate of this study was 60.8% and 40.8% of the patients who had continued KD at 6 and 12 months, respectively, which was consistent with previous studies as well 24–26 . There was a statistically significant association between the retention rate and the outcome of seizures, so lack of compliance could be attributed to ineffectiveness or intolerance.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Nevertheless, the response rate observed in our study was lower than that reported by other studies which ranged between 70% and 90% 22,23 . The retention rate of this study was 60.8% and 40.8% of the patients who had continued KD at 6 and 12 months, respectively, which was consistent with previous studies as well 24–26 . There was a statistically significant association between the retention rate and the outcome of seizures, so lack of compliance could be attributed to ineffectiveness or intolerance.…”
Section: Discussionsupporting
confidence: 86%
“…22,23 The retention rate of this study was 60.8% and 40.8% of the patients who had continued KD at 6 and 12 months, respectively, which was consistent with previous studies as well. [24][25][26] There was a statistically significant association between the retention rate and the outcome of seizures, so lack of compliance could be attributed to ineffectiveness or intolerance. A smartphone application was used in our follow-up process, which facilitates the communication between patients and the management team, improves communication efficiency, and increases patient compliance; this might be explained by the high retention rate (100%) at 3 months in this study; this retention rate is higher than that observed in the study conducted by Mei Yu et al 27 Our study had shown that the gender, the duration of seizure onset, the starting age of KD treatment, and BMI Z-score in children with epilepsy had no significant relationship with the effect, which was similar to previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies examining the prognosis of patients who received KD focused primarily on seizure control outcomes. 4,[9][10][11] Our study demonstrates the efficacy of the KD in children with various types of drug-resistant epilepsy. Few studies have addressed the long-term outcomes of children on the KD and strategies for minimizing relapse occurrence.…”
Section: Discussionmentioning
confidence: 64%
“…Most previous studies examining the prognosis of patients who received KD focused primarily on seizure control outcomes 4,9–11 . Our study demonstrates the efficacy of the KD in children with various types of drug‐resistant epilepsy.…”
Section: Discussionmentioning
confidence: 67%